Sedimentology of the Moosebar Tongue and Bounding Strata, Lower Cretaceous Blairmore Group, South-Central Foothills, Alberta - Taylor, David R. (My University, 1981)
This thesis provides detailed sedimentological descriptions and generalized interpretations of depositional environments within the Lower Cretaceous Blairmore Group of Alberta. In earliest Blairmore time (Hauterivian - Barremian ?), uplift to the west resulted in a period of extensive pedimentation and deposition of coarse clastics of the Cadomin Formation. Paleogeographic reconstructions indicate that a series of humid-climate alluvial fans to the west fed a NW flowing trunk stream to the east that occupied the Spirit River Channel. In the Spirit River Channel, a series of lenticular channels filled with conglomerate and coarse-grained sandstone suggest that deposition was in pebbly braided and low sinuosity sandy fluvial environments.
Subsequent to deposition of the Cadomin Formation (Aptian time), finer grained sandstones and shales of the Gladstone Formation were deposited. Thicker sandstones commonly contain lateral accretion surfaces and are rooted in their uppermost parts indicating deposition in a high sinuosity meandering fluvial environment. Paleocurrent data suggest that the ancient rivers flowed NNW, debouching into a boreal sea to the north. The uppermost part of the Gladstone Formation contains nonmarine to brackish fauna and is interpreted as having been deposited in a large brackish lake analagous to modern Lake Maracaibo of Venezuela.
In early Albian time, a boreal sea (Clearwater Sea) transgressed southward and covered most of the central Alberta and northeastern British Columbia. Marine sandstones and shales of the Moosebar Tongue were deposited at this time. In the study area, the shoreline of the Clearwater Sea was oriented ENE-WSW and coarsening-upward sequences within the Moosebar Tongue indicate that the shoreline advanced by the progradation of nearshore bars. Deposition was in a high energy, storm-dominated system. Bordering the Clearwater Sea to the south was the large brackish lake in which sediments of the uppermost part of the Gladstone Formation were deposited.
Following regression of the boreal sea from the Foothills region in early to middle Albian time, a coastal plain environment prevailed within the depositional basin. As regression continued, the coastal plain sequence was overlain by a fluvial sequence deposited by large-scale meandering rivers. Paleocurrent data indicate that the rivers flowed generally northwards, subparallel to the foreland basin, and debouched into an Arctic embayment.
Keywords: Geology; Geology